Feed blocks as a supplement for goat kids grazing natural Tunisian rangeland during the dry season (ANIMAL FEED SCIENCE AND TECHNOLOGY, 2006)
Two experiments were conducted to investigate the effects of PEG and feed blocks on digestion of shrub species consumed by goats (experiment 1) and kid growth while browsing during the dry season (experiment 2). In experiment 1, in vitro gas production was determined using a rumen fermenter. Six shrub species were incubated separately (Erica arborea, Phillyrea angustifolia, Pistacia lentiscus, Myrtus communis, Quercus suber, and Viburnum tinus). Effects of polyethylene glycol (PEG 4000) and feed block supply were investigated. In experiment 2, 21 local kids, 18.75 (+/- 1.4) kg body weight (BW) were allowed to browse in shrub-lands and allocated to three treatments in a production trial lasting 147 days (July-December). Control group receive no supplement, whereas the two other groups received either PEG-free (13) or PEG-containing feed blocks (B-PEG). All shrubs were low in crude protein (59-91 g kg(-1) dry matter) but high in total condensed tannins; mean content was 43 g kg(-1) DM (8.8-65) for bound condensed tannin and 205 g kg(-1) DM (10.8-363) for free condensed tannin. Gas volume produced after 24 h differed among shrub species (P < 0.05). V tinus produced the highest volume (77.8 ml g(-1) organic matter) and Q. suber the lowest (35 ml g-1 OM). The mean rate of fermentation was 0.135h(-1) (0.121-0.150 h(-1)). PEG addition increased gas production by 48.5%, volatile fatty acid by 38.4% and organic matter fermented by 41.7% of the mixture of shrubs (P < 0.05). In the practical trial, the use of blocks with and without PEG avoided BW loss of the goats under dry season. While the control group lost 19 g day(-1), the bloc supplemented groups grew at 12 g day(-1) (-PEG) and 24 (+PEG) g day(-1). (c) 2005 Elsevier B.V. All rights reserved.

In vitro gas production and its relationship to in situ disappearance and chemical composition of some Mediterranean browse species (Animal Feed Science and Technology, 2005)
In vitro gas production of seven species (i.e., Arbutus unedo, Calycotum villosa, Erica arborea, Phillyrea angustifolia, Pistacia lentiscus, Myrtus communis, Quercus suber) that are widely browsed by goats were measured through 120 h and related to in situ dry matter disappearance (DMD) and chemical composition. Three goats fitted with ruminal cannulae were used for the in vitro and in situ studies. Browses varied in their crude protein (CP: 55–221 g/kg DM) and neutral detergent fibre (360–551 g/kg DM) contents. High levels of total condensed tannins (TCT) were observed in Pistacia lentiscus, and the lowest levels were in Calycotum villosa and Phillyrea angustifolia. The browses varied widely in potential (145.7–224.0 ml/g DM) and fractional rates (0.038–0.075/h) of gas production, and there were differences among species in DMD (P < 0.05). Gas production at 24 h was positively correlated (P < 0.05) with in situ DM disappearance and CP content, but negatively correlated (P < 0.05) to acid detergent lignin (ADL), free condensed tannins (FCT) and TCT contents. The fractional rate of fermentation (μ) was negatively related (P < 0.05) to FCT (r = −0.81) and TCT (r = −0.83), whereas DMD was only related to acid detergent fibre and ADL content. Results support combined use of gas production and in situ techniques to determine the nutritive value of feeds containing phenolic compounds.